The potential of accessible tourism for sustainable development of local communities in northern Pakistan - Hassaan Ahmed; Hadiqa Riaz (Journal of Entrepreneurship, Management and Innovation, 2024)
PURPOSE: Accessible tourism holds significant importance for local communities as it is a cornerstone for fostering inclusivity and equal participation in the tourism industry. Recognizing the growing global emphasis on inclusivity, especially for individuals with diverse needs, this research aims to explore the multifaceted impacts of accessible tourism on the sustainable development of local communities in the northern areas of Pakistan. Additionally, the study assesses the moderating role of destination image between accessible tourism dimensions and the sustainable development of local communities. Given that destinations heavily rely on tourism to fulfill their socio-economic needs, it becomes imperative to evaluate the potential transformative impact of accessible tourism on their sustainable development. METHODOLOGY: A self-administered survey was completed using a two-stage sampling approach with 321 tourists and 321 local residents from five tourist destinations in northern Pakistan. Subsequently, the collected data were analyzed using Structural Equation Modeling (SEM) to test the proposed hypotheses. FINDINGS: The results show the significance of all four dimensions of accessible tourism (accessible core resources and attractors, accessible supporting factors and resources, accessible qualifying and amplifying determinants, and destination planning and management) in the sustainable development of local communities. The moderation assessment further confirms that destination image strengthens the relationship between accessible core resources and attractors, contributing to the sustainable development of local communities. However, destination image was found to have a negative moderating effect between accessible qualifying and amplifying determinants and the sustainable development of local communities. IMPLICATIONS: Empirical findings offer fresh insights for destination planners and policymakers in the tourism industry. These insights pertain to the effective utilization of accessible tourism practices, which can significantly contribute to the sustainable development of destinations. Additionally, tourism businesses can leverage the research to attract a broader segment of tourists, increase profitability, and enhance tourist satisfaction by implementing accessible practices and services. Understanding the moderating role of destination image can further guide them in crafting responsible tourism narratives that resonate with diverse travelers. ORIGINALITY AND VALUE: The study marks an initial attempt to explain how destinations, particularly those heavily reliant on tourism, can strategically leverage accessible tourism as a crucial factor in fostering sustainable community development.